MASALAH-MASALAH SOSIAL YANG DIALAMI SISWA BERDASARKAN TINGKAT EKONOMI ORANGTUA KELAS VIII DI SMPN 4 PEKANBARU - Gusthia Fischarini; Raja Arlizon; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study is to find out the general picture of the social problems of students, the picture of social problems of students with very high economic background, the picture of social problems of students with high economic background, the picture of social problems of students with a medium economic background , And to know the description of social problems of students with low economic background, in SMP Negeri 4 Pekanbaru. Technique of data retrieval in this research using questionnaire method, to collect data of social problem that experienced by student based on economic level of parent. Research subjects are all students of class VIII SMP Negeri 4 Pekanbaru which amounted to 361 people. Determination of sample by using Saturation Sampling technique. Data analysis was done by using qualitative method with descriptive approach. Where researchers chose class VIII students because of the results of the phenomenon in the field. The results showed that the social problems experienced by students in general are in the category no problem that is equal to 48.75%, social problems with very high economic background is in the category enough problematic 60.00%, social problems with economic background High is in the category of no problem at 50.00%, social problems with economic background are in the category of quite problematic 55.00%, and on social problems with low economic background is in the category no problem of 48.79%.Key Words: Social problems, economic